2008
DOI: 10.1021/tx800035b
|View full text |Cite
|
Sign up to set email alerts
|

hERG Potassium Channels and the Structural Basis of Drug-Induced Arrhythmias

Abstract: hERG potassium channels have a critical role in the normal electrical activity of the heart. The block of hERG channels can cause the drug-induced form of long QT syndrome, a cardiac disorder that carries an increased risk of cardiac arrhythmias and sudden death. hERG channels are extraordinarily sensitive to block by large numbers of structurally diverse drugs. In previous years, the risk of compounds causing this cardiotoxic side effect has been a common reason for the failure of compounds in preclinical saf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
84
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(85 citation statements)
references
References 65 publications
1
84
0
Order By: Relevance
“…4 However, measuring only one type of current for screening drug-induced effects for a range of channels is expected to give faulty results. An in vitro cardiac safety assay that can integrate more than only the hERG ion channel current is, therefore, a great concern of the pharmaceutical industry to achieve a better drug regulatory program.…”
Section: Introductionmentioning
confidence: 99%
“…4 However, measuring only one type of current for screening drug-induced effects for a range of channels is expected to give faulty results. An in vitro cardiac safety assay that can integrate more than only the hERG ion channel current is, therefore, a great concern of the pharmaceutical industry to achieve a better drug regulatory program.…”
Section: Introductionmentioning
confidence: 99%
“…4 Now, testing the hERG blockade is a routine process at an early stage of drug development before clinical testing. 5 For these reasons, several attempts have been made to find out the binding mechanism of the hERG blockers. Above all, many studies have discovered the hERG channel structure, which has helped researchers understand about drug binding.…”
Section: Introductionmentioning
confidence: 99%
“…Ala-scanning mutagenesis studies have identified critical residues interacting with drugs on those transmembranes. 5 Those are two aromatic residues and two polar residues : Tyr 652 and Phe 656 on S6 and Thr 623 and Ser 624 on the pore helix. 5 Some residues are also known as interacting with hERG blockers by the indirect method through an allosteric effect.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations